Risk Governance in Non-financial Companies - Mombeshora, Martin (2013)
Following the recent financial crisis, risk governance has been brought to the forefront as a prevalent issue in both financial and large complex non-financial companies. This research project takes the form of a cross-sectional study and aims to further understand this issue by investigating the determinates of risk governance mechanisms and reporting structures in large, listed non-financial companies that are listed on the London Stock Exchange’s FTSE100 index. Initially, thematic content analysis was performed to collect data from the company annual reports. Focusing on the 2012 operating period, an index was created to assess the level of risk governance mechanism adoption across the firms. The index consisted of nine variables of risk governance mechanisms, which included the presence of a group level risk role and risk committee, they served to provide an indication of the presence of risk governance within the firms being studied. The research project adopted a mixed methods methodology which included both qualitative and quantitative research methods. Based on a set of 17 independent variables, the determinants of risk governance adoption were investigated. Regression analysis was then performed and only two of the variables, liquidity ratio and debt ratio were found to be statistically relevant determinants. Out of five developed hypothesises, hypothesis 1, which states that there is a positive relationship between financial characteristics and risk governance mechanisms, was proven to be correct. This suggests that financial characteristics are a determinant of the adoption of risk governance mechanisms within large non-financial firms.